2004
DOI: 10.1080/02772240400007039
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal depuration in flat tree oystersisognomon alatusunder field and laboratory conditions

Abstract: Oysters Isognomon alatus containing high concentrations of Zn, Cu, Pb and Cd were collected from the Sepang Besar River, and transferred to the Sepang Kecil River where the native oysters contain low metal concentrations. Concentrations of heavy metals in oysters were measured monthly over six months. The concentrations of all metals decreased significantly ( p<0.05) for Cd 87%, Pb 83%, Cu 78%, and Zn 59%. In addition, metal depuration in oysters was investigated under laboratory conditions. Oysters were expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Several trials make depuration by transplanting the clams or oysters in another clean field (Saed et al, 2004;Gabr and Gab-Alla, 2008). But these trials needed long periods for depuration that ranged from 50 days to 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several trials make depuration by transplanting the clams or oysters in another clean field (Saed et al, 2004;Gabr and Gab-Alla, 2008). But these trials needed long periods for depuration that ranged from 50 days to 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…But these trials needed long periods for depuration that ranged from 50 days to 6 months. Other studies under took depuration in different experimental conditions (EL-Shenawy, 2004;Saed et al, 2004;El-Gamal, 2011). They found that it needs 2-32 days for complete depuration.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the intense anthropogenic activity and the significant population in the area, the economic importance of the species, and the public-health concerns regarding raw consumption of oysters, we suggest that studies of heavy-metal concentrations in C. gigas farmed in this region be carried out periodically. Depuration, moving oyster racks to lower metal levels sites, and use of sterilized water to clean oysters before consumption are also possible strategies in lowering metal contents (Okazaki & Panietz, 1981;Katayon et al, 2007;Wang & Wang, 2014). CAdenA-CáRdenAS, l., l. méndeZ-RodRíGueZ, T. ZenTeno-SAVín, J.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, only limited biomonitoring studies on trace metals were reported using I. alatus, except for those reported by some researchers (Campos 1988;Jaffe et al 1998;Sbriz et al 1998;Saed et al 2001Saed et al , 2004. Therefore, the objective of the present study was to determine the bioavailabilities and contamination by Fe, Ni, and Cu in the four different soft tissues (mantle plus gill, muscle, byssus, and remaining soft tissue) of I. alatus collected from seven geographical populations in the mangrove areas of Peninsular Malaysia.…”
Section: Introductionmentioning
confidence: 97%
“…In this study, the flat tree oysters Isognomon alatus (Family: Isognomonidae) was focused upon since they are potential candidates for heavy metal biomonitoring studies and they can be widely found along the mangrove estuaries of the Sepang and Lukut areas in the west coast of Peninsular Malaysia. Earlier, Saed et al (2001) studied metal concentrations in oysters after exposure to pig farm effluents, and Saed et al (2004) reported metal depuration using I. alatus under field and laboratory conditions. The above two studies indicated that I. alatus has a strong capability of accumulation and depuration of Cd, Cu, Pb, and Zn and therefore could be used as a suitable biomonitor.…”
Section: Introductionmentioning
confidence: 98%